Dermatological Adverse Events in Prostate Cancer Patients Treated with the Androgen Receptor Inhibitor Apalutamide. Issue 5 (12th May 2022) - Pan, Alexander; Reingold, Rachel E.; Zhao, Jimmy L.; Moy, Andrea; Kraehenbuehl, Lukas; Dranitsaris, George; McBride, Sean M.; Scher, Howard I.; Kollmeier, Marisa A.; Xiao, Han; Rathkopf, Dana E.; Lacouture, Mario E.
Abstract : Purpose: Patients with prostate cancer (PCa) treated with apalutamide frequently develop rash. We aim to characterize apalutamide-related dermatological adverse events (dAEs) and management. Materials and Methods: We assessed 303 patients with PCa treated with apalutamide. DAE frequency and time to onset were calculated and clinicopathological features and management described. Associations between dAE occurrence and clinical trial participation, as well as abiraterone/prednisone exposure were detected using logistic regression models. Results: Seventy-one (23.4%) patients had all-grade dAE occurring at a median of 77 (IQR: 30–135) days post-exposure. Twenty (6.6%) dAE-related therapy interruptions included: 8 (2.6%) with dose maintained on rechallenge, 7 (2.3%) with dose reduction and 5 (1.7%) with discontinuation. Common dAEs were maculopapular rashes (33.8%) and xerosis (32.4%). Seven (77.8%) of 9 histological analyses of skin biopsies supported a drug reaction. No significant differences in laboratory hematological, hepatic and renal function were detected between dAE and no dAE cohorts. Most treated grade 1/2 dAEs (29, 40.8%) required topical steroids (14, 19.7%); few required oral steroids (3, 4.2%) ± oral antihistamines. Most grade 3 dAEs (8, 11.3%) required oral/topical steroids (5, 7.0%); few required topical steroids (3, 4.2%) ± oral antihistamines. Clinical trial patients (180, 59.4%) were more likely to report dAEs than those in the off-trial setting (OR=5.1 [95% CI 2.55–10.12]; p <0.001). Of clinical trial patients, concomitant abiraterone/prednisone recipients (109 of 180, 60.6%) were more likely to report dAEs (OR=3.1 [95% CI 1.53–6.17]; p=0.002). Conclusions: Apalutamide-related dAEs are frequent and can be managed with topical ± oral steroids. With expanded approval of apalutamide, dAE identification and management are essential.